Pengaruh Motivasi, Lingkungan Kerja, dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan di CV. Dwijaya Bersama Satu - Sandi Restu Widhi; Jaelani Jaelani (LPPM Politeknik Pratama, 2026)
This study was motivated by the importance of employee job satisfaction in supporting productivity, loyalty, and organizational success. Low work motivation, uncomfortable working conditions, and limited career development opportunities can reduce employee job satisfaction levels. This study aimed to analyze the influence of motivation, work environment, and career development on employee job satisfaction at CV. Dwijaya Bersama Satu. The study used a quantitative approach with a causal associative research design. The research population consisted of 35 employees, and all respondents were selected using a saturated sampling technique. Data collection was conducted through questionnaires, observation, and documentation. Data analysis used SPSS version 27 through validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results showed that motivation, work environment, and career development had a positive and significant influence on employee job satisfaction, both partially and simultaneously. The adjusted R Square value of 0,645 indicates that motivation, work environment, and career development were able to explain employee job satisfaction by 64.5%. The work environment variable became the most dominant factor in improving employee job satisfaction within the company. The findings are expected to become evaluation material for companies in improving human resource management quality through better motivation, supportive workplaces, and directed career development programs sustainably.